Citrus essential oils: Extraction, composition, biological activities, and applications - Xinyi Liu; Ke Fang; Xianzhong Lv; Meng Guo; Yuting Tang; Jiao Wang; Wanpeng Xi (Trends in Food Science & Technology, 2026)

Ambient PM2.5 exposure and sleep quality: Evidence from circadian DNA methylation signatures in a population-based study - Yuting Wang; Shuzhen Liu; Jiahui Rong; Yaxin Luo; Siyuan Niu; Peifeng Guo; Xu Tang; Yujian Liang; Xiaoting Mo; Linhai Zhao; Shiwen Jiang; Tiantian Gu; et al. (Journal of Hazardous Materials, 2026)

High-throughput nucleic acid extraction using a pipette-tip annular magnetic separator integrated with real-time fluorescent RPA for rapid detection of Burkholderia gladioli pv. cocovenenans - Jiali Wang; Yuting Su; Yaru Chen; Lei Tang; Dongmei Li; Wenchao Du; Yumin Shen; Fangfang Zhou; Hong Duan; Baoguo Sun; Gang Chen; Lingyan Zheng (Food Bioscience, 2026)

Short- and medium-term exposure to ambient air pollutants and severity of obstructive sleep apnea: A population-based study in Nanjing - Xia Tang; Haili Ren; Yuting Huang; Ting Xu; Daling Hu; Yizhang Xia; Tongda Xu; Quan Wang; Jiemiao Shen; Minghui Ji (Environmental Research, 2026)

Hydrologic and sediment responses to vegetation changes from Eagleson's ecohydrological perspective - Zhiqiang Tang; Qiang Liu; Liqiao Liang; Jifa Qin; Jianfei Wu; Yuting Yang; Xuan Wang; Chunhui Li (CATENA, 2026)

Enhanced electron transfer via Fe-Mn synergy in self-nitrogen biochar for rapid and efficient Cr(VI) removal - Yuting Zhang; Li Zhang; Yuwei Tang; Yilong Li; Weibin Sun; Zihao Yang; Jinchunzi Li; Shuang Liang; Jing Zhou (Biomass and Bioenergy, 2026)

Effect of microplastics on arsenic transport in shallow groundwater of coastal transition zones - Yizi Hua; Yuan Xue; Zhi Li; Yuting Zhang; Qinglong Liu; Linan Liu; Jingchun Tang (Water Research, 2026)

DDT biotransformation by a delta-class glutathione S-transferase underlies tolerance in honey bees - Huali Song; Xiangyou Tang; Jingsong Hu; Jing Zhang; Mingyu Song; Yaohui Li; Yuting Ma; Zhengang Ma; Zeyang Zhou; Jinshan Xu (Pesticide Biochemistry and Physiology, 2026)

Enhancing large-scale streamflow prediction by coupling structural inductive bias with meta-learning - Xuan Tang; Yuting Zhao; Yuan Yu; MingRui Yu; Guanghua Qin; Hongxia Li (Journal of Hydrology, 2026)

Perfluorooctanoic acid (PFOA) disrupts marine carbon sequestration potential of diatom Phaeodactylum tricornutum by regulating carbon-silicon coupling - Zhi Li; Yizi Hua; Yuan Xue; Linan Liu; Yuting Zhang; Lan Wang; Gang Wang; Qiang Li; Jingchun Tang (Journal of Hazardous Materials, 2026)

Methane production from caproic acid fermentation residuals of food waste in anerobic dynamic membrane bioreactor: A promising route for organic waste valorization - Yunhui Pu; Jingyun Chen; Dan Xu; Yang Luo; Bujiamu Ayi; Yang Li; Yuting Kuang; Qingyuan Wang; Jialing Tang; Abdelfatah Abomohra (Journal of Environmental Management, 2026)

High-efficiency recovery of lithium from waste lithium-ion batteries using a steam-assisted calcium-based carbon thermal reduction process - Yuting Wang; Jianjun Cai; Xingying Tang; Yumeng Wu; Jiafeng Zhang (Chemical Engineering Journal, 2026)

A new interdisciplinary approach for identifying the lower Yellow River's sediments and flow path beyond historical documents - Tianyu Shi; Peng Chen; Xiaodong Miao; Xiangtao Tang; A.O. Sawakuchi; Yuting Liang; Laiying Jin; Yuming Su (CATENA, 2026)

Comparative effects of digestion residue-derived and corn straw biochar on free-living diazotrophs in nitrogen-deficient calcareous purple soil - Junwen Zhao; Yuting Chen; Haiyan Zhang; Yulan Chen; Bing Li; Muhammad Bilal Khan; Yingjie Wu; Xiaoyan Tang; Huanxiu Li; Rong Huang; Qiang Xu; Qiquan Li; et al. (Biology and Fertility of Soils, 2026)

Label-free cell phenotypic profiling of sphingosine-1-phosphate receptor 1 and discovery of its agonist from natural products - Xiyi Wang; Yuchang Sun; Hongming Tang; Tao Hou; Han Zhou; Xiaomin Xie; Yuting Li; Pan Wang; Yang Han; Lai Wei; Fangfang Xu; Yanfang Liu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Genome-wide identification of IiSPL gene family and IiSPL9 functional exploration - Jinyu Zheng; Yuting Zhang; Zhihua Liu; Limi Tang; Bowen Duan; Zirong Wang; Tao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Artemisinin derivative SM934 targets α-enolase to inhibit PEP-mediated TAK1 stabilization and inflammation - Jun Pan; Yuwei Zhang; Zhiwei Du; Yuanyuan Huang; Yu Wang; Miya Su; Yuting Cai; Weiya Xu; Lili Chen; Chengdong Huang; Di Cui; Dongsheng Chen; et al. (Science China Life Sciences, 2026)

A review of machine learning applications in soil heavy-metal remediation: material design, process optimization, and future challenges - Minsheng Fu; Zhipeng Tang; Yuting Liu; Yumeng Zhou; Chenyang Zhang (Environmental Geochemistry and Health, 2026)

Nitrogen and Sulfur Deposition Contributes to Soil Acidity Variation Under Different Land use Patterns Over Decade in a Subtropical Small Watershed - Hanchen Wu; Xiaobin Guo; Li Tang; Yuting Dai; Wenqian Jiang; Haoyu Fu; Pei Luo; Jianlin Shen; Jinshui Wu (Water, Air, & Soil Pollution, 2026)

Efficient electronic configuration and adsorption energy balance enabled by trimetallic nanozymes: Toward AI-powered visual identification of Pseudomonas aeruginosa - Huiqi Yan; Le Zhou; Wenyan Tang; Jinbo Cao; Li Wang; Qingshuang Luo; Yuting Zhuang (Chemical Engineering Journal, 2026)

The Potential Anticancer Mechanisms of Probiotics: A Comprehensive Review - Chao Tang; Yue Qian; Shiyao Jia; Junyan Zhang; Yao Zhang; Yuting Ren; Huimin Yong; Jingguo Xu; Juan Kan; Jun Liu (Probiotics and Antimicrobial Proteins, 2026)

Granulated organic amendments enhance soil organic carbon sequestration and saturation by modulating functional pools in infertile paddy soils - Yan Li; Lijia Liu; Yingnan Xian; Haoyu Fu; Li Tang; Yuting Dai; Wei Gao; Yan Li; Shoulong Liu; Junjian Li; Xiaobin Guo; Jinshui Wu (Plant and Soil, 2026)

A General Kinematic Brain Injury Criterion Combining Translational and Rotational Effects - Yuting Zhang; Da Teng; Zexuan Chen; Bao Yang; Zhenyu Jiang; Yiping Liu; Zejia Liu; Licheng Zhou; Liqun Tang (Annals of Biomedical Engineering, 2026)

Metabolomic profiling reveals activity-correlated chemotypes and strain-specific metabolites in mangrove-derived actinomycetes - Bonan Yan; Ming Chen; Ling Li; Peixi Zhang; Ki Shi; Li Guo; Yixin Tang; Chunlan Li; Yanjun Di; Chen Zhu; Yuting Wu; Chenlei Lian; et al. (Natural Product Research, 2026)

How keystone taxa shape sediment carbon accumulation during lake restoration: A new insight from asynchronous regime shifts of community structure and function - Feng Yu; Wenlong Zhang; Zikang Tang; Yajie Zhu; Yuting Yan; Yi Li (Water Research, 2026)

Humic acid modulates Fe(II) mediated chromium reduction in simulated marine-terrestrial interlaced zones: A double-edged sword effect - Yuan Xue; Yizi Hua; Zhi Li; Yuting Zhang; Linan Liu; Jingchun Tang (Journal of Hazardous Materials, 2026)

Optoelectronic synaptic transistor array based on CsPbBr3/grating-patterned IDTBT heterojunctions for neuromorphic visual fatigue sensing - Jiajie Hong; Zhiqian Wei; Zunxian Yang; Yue Chen; Luxi Yuan; Shangwei Ye; Xudong Jiang; Yuting Bai; Benfang Liu; Zhiyu Yuan; Wenxin Zhang; Jie Li; et al. (Chemical Engineering Journal, 2026)

Erratum to: Artemisinin analogue SM934 protects against lupus-associated antiphospholipid syndrome via activation of Nrf2 and its targets - Zemin Lin; Yuting Liu; Li Chen; Shiqi Cao; Yueteng Huang; Xiaoqian Yang; Fenghua Zhu; Wei Tang; Shijun He; Jianping Zuo (Science China Life Sciences, 2026)

Regulatory mechanisms of spatiotemporal variations in aboveground and belowground net primary production in global terrestrial ecosystems - Tao Zhou; Yanting Xiong; Zhihan Yang; Yuting Hou; Yuqing Zhang; Dan Liao; Xiaodong Wang; Dinghui Xu; Pingfeng Li; Peng Hou; Wenji Zhao; Guo Chen; et al. (Agricultural and Forest Meteorology, 2026)

Disentangling phytoplankton regime shifts and ecosystem stability under water diversion: Insights from functional traits and trophic interactions in a mesocosm experiment - Yajie Zhu; Wenlong Zhang; Feng Yu; Zikang Tang; Yuting Yan; Ruoyu Liu; Jiaxin Tong; Yi Li (Water Research, 2026)

Short-term black carbon exposure impairs mental health and DNA methylation signatures of mitochondrial carrier genes - Shuzhen Liu; Yaxin Luo; Jiansheng Cai; Yuting Wang; Jiahui Rong; Xiaoting Mo; Yujian Liang; Zeyan Ye; Xu Tang; Siyuan Niu; Tiantian Zhang; Lei Luo; et al. (Journal of Hazardous Materials, 2026)

Residential greenness and metabolic syndrome among older adults: exploring the mediating effects of physical activity and sedentary time - Shuhui Dai; Lu Fang; Yuting Zhang; Hazizi Duoliken; Man Rao; Jiayi Li; Shanshan Yin; Mingjuan Jin; Jianbing Wang; Kun Chen; Mengling Tang (Environmental Research, 2026)

Can river damming amplify or dampen climate-driven changes in fluvial sediment transport? A case study of Jinsha river basin - Jianfei Wu; Qiang Liu; Liqiao Liang; Yuting Yang; Zhiqiang Tang; Jifa Qin; Shuzhen Li; Xuan Wang; Chunhui Li (Journal of Hydrology, 2026)

RAD51 m6A and PARylation modification orchestrate benzene-induced haematological toxicity - Lin Chen; Fengzhen Cui; Han Li; YuTao Zeng; Zhongming Wu; Weitian Chen; Qiaosheng Wen; Chunnian You; Yunqiang Xu; Lei Sun; Mingwei Sun; Qian Sun; et al. (Journal of Hazardous Materials, 2026)

Effects of a forage-native multi-PGPM consortium symbiotic system on rhizosphere ecology and microbial regulation for remediating PAHs-contaminated very-high-altitude coal mines - Deyu Dong; Zhanling Xie; Bao Wang; Weiyou Ou; Yongpeng Tang; Jiabao Yang; Yuting Guo; Xueting Fa (Journal of Hazardous Materials, 2026)

Multi-scale insights into steel slag-derived dual functional materials for enhanced hydrogen production and CO2 capture in biomass sorption-enhanced gasification - Hongyu Liu; Yuting Tang; Xiaoqian Ma; Jiehong Tang; Wenchang Yue; Zhuofan Chen; Zejie Zheng (Fuel, 2026)

Measurement and spatio-temporal evolution analysis of high-quality development level in China's marine economy - SHA Xiujuan; WANG Yuting; TANG Huimin (Regional Studies in Marine Science, 2025)

Community interactions drive phytoplankton regime shifts in interconnected water bodies: Insights from space for time approach - Yajie Zhu; Wenlong Zhang; Yasong Chen; Feng Yu; Zikang Tang; Zexin Li; Yuting Yan (Journal of Environmental Management, 2025)

Enhancement of propane activation and aromatization through DME participation over Ga modified HZSM-5 - Xia Li; Pengfei Li; Yujie Xie; Yuting Dai; Kui Tang; Xumeng Huang; Caixia Hu; Yanyan Chen; Peng He; Jianguo Wang (Fuel, 2025)

Dual regulatory mechanism of microplastics surface electric field in arsenic adsorption: Experimental and computational insights - Fengxin Zhao; Yaowu Zhang; Ying Tang; Xinmin Liu; Tong Xu; Yuting Feng; Hang Li (Chemical Engineering Journal, 2025)

Cortical contribution related to top-down regulation in tone perception - Xiaotong Zhang; Yuting Tang; Houmin Wang; Zijian Huang; Wahou Tai; Soitou Wong; Zhuoming Chen; Jinyi Long (Cognitive Neurodynamics, 2025)

Assessing future flood risk using remote sensing and explainable machine learning: A case study in the Beijing-Tianjin-Hebei region - Siying Li; Yi Tang; Yuting Zhao; Xiaojun Ning; Yifan Zhang; Siran Lv; Chenshu Liu (Remote Sensing Applications: Society and Environment, 2025)

Fenton reaction-enhanced mild photothermal therapy for cancer suppression with a multifunctional platform - Kaiye Wang; Yuting Jia; Xiaohan Liu; Limeng Pan; Mingwan Shi; Wei Pan; Na Li; Bo Tang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Determining the differences in O3-NOx-VOCs sensitivity between sauna and roast days - Yuting Liu; Yinghong Wang; Yusi Liu; Mengtian Cheng; Baoxian Liu; Tao Song; Bo Hu; Dan Yao; Miao Yu; Yu Shi; Guiqian Tang; Yuesi Wang (Journal of Environmental Sciences, 2025)

Hyaluronic acid-modified carbon dot-incorporated multimetallic hydrotalcite for synergistic cancer immunotherapy via tumor microenvironment reprogramming - Yuting Lu; Guanghao Li; Sihan Tang; Hui Zhang; Kailei Liu; Zhiqiang Wang; Guanghui Tan; Yingxue Jin (Chemical Engineering Journal, 2025)

Co-occurrence networks dominated by rare and abundant fungal species influence the potential function of fungal communities in Eucalyptus urophylla plantations under successive planting - Yuting Yang; Aoyu Ling; Lingyue Zhu; Qinzhan Wu; Kangting Huang; Dexu Zhang; Zhengye Wang; Zuoyu Qin; Lichao Wu; Jian Tang (Applied Soil Ecology, 2025)

Evaluating green total factor productivity in Chinese port listed companies based on biased technological change perspective - Yuting Zheng; Xiongjun Yuan; Dan Liu; Jingying Tang; Huishan Fu (Environment, Development and Sustainability, 2025)

LncRNA SNHG15 sponges miR-3143/FOXO3 to regulate autophagy in ovarian dysfunction induced by benzene exposure - Zhongming Ye; Qihao Huang; Haipeng Wu; Shimei Wang; Boxin Li; Minjuan Zeng; Tikeng Jiang; Biyan Ye; Yixian Wei; Lei Sun; Shaoying Wang; Yutao Zeng; et al. (Toxicology Letters, 2025)

Nucleolin alleviates endotoxemia-induced myocardial dysfunction via inhibiting Drp1-mediated mitochondrial fission - Ludong Yuan; Yuting Tang; Leijing Yin; Xiaofang Lin; Pengfei Liang; Bimei Jiang (Tissue and Cell, 2025)

PDHA1-mediated H3K18 lactylation is involved in arsenic-induced nonalcoholic fatty liver disease by activating the CD36–NLRP3 inflammasome axis - Han Li; Zhenyang Li; Lin Chen; Xiaoshan Peng; Dapeng Wang; Qian Sun; Yuting Chen; Aihua Zhang; Qizhan Liu; Huanwen Tang (Journal of Hazardous Materials, 2025)

Application of CaO-Ni bifunctional material in the adsorption - enhanced pyrolysis of municipal solid waste - Haohang Huang; Yuting Tang; Hongyu Liu; Jiehong Tang; Ziwei Sun; Zejie Zheng; Xiaoqian Ma (Journal of Environmental Chemical Engineering, 2025)

Trained membrane-decorated smart nanocage: A broad-spectrum antibacterial system inducing bacterial ferroptosis via metabolic reprogramming and ROS cascade reaction - Feng Lu; Huiqun Hu; Xinhui Wu; Shishuo Li; Hubing Wang; Yimin Liu; Wenting Zhang; Yuting Tang; Lingzhi Ding; Zhaobo Zhang; Pengfei Lei; Mingxuan Feng (Chemical Engineering Journal, 2025)

Exploring the links between wetland design parameters, hydraulic behaviors, and treatment performance using an improved analysis framework - Bochao Zhang; Junzhe Luo; Yuting Zhang; Jiaer Wang; Chi Tang; Yufeng Luo; Yuanlai Cui (Journal of Hydrology, 2025)

Cigarette smoke-induced PPAR signaling dysregulation accelerates Alzheimer's disease pathogenesis and cognitive decline in 5xFAD mice - Yunqi Xie; Haochen Wang; Yajie Zhang; Bingbing Lin; Yuting Chen; Kai Li; Huanwen Tang; Qian Sun (Food and Chemical Toxicology, 2025)

Response of Soil Phosphorus Fractions and Available Phosphorus to Phosphorus Plus Silicon Addition in Alpine Meadows - Yuxin Tang; Danghui Xu; Yuting Yang; Baiying Huang; Xiangwen Fang; Guangqian Yao; Wenhong Zhou; Yuqi Wu (Journal of Soil Science and Plant Nutrition, 2025)

Effects of Saccharomycopsis fibuligera on the formation of flavor substances and functional enzymes during turbid rice wine brewing - Lanchai Chen; Jingwen Dai; Ya Shu; Yuting Zou; Zhuolin Yi; Tianzhu Zhang; Wenliang Xiang; Jie Tang; Shu Bao; Hai Zhao; Qing Zhang (International Journal of Food Microbiology, 2025)

Multi-mode probe based on dual colorimetric and photothermal later flow immunoassay for the ultrasensitive determination of benzo[a]pyrene in vegetable oils - Yuting Yuan; Xiaoqian Tang; Liangxiao Zhang; Qi Zhang; Fei Ma; Peiwu Li (Food Chemistry, 2025)

Dual-opto-CRISPRi-mediated dynamic regulation of fructose metabolism for high-efficiency D-allulose biosynthesis in E. coli - Yuwei Wang; Yingmengyu Qin; Tongjian Li; Dandan Tang; Yuting Lu; Wei Liu; Ling Jiang (Food Bioscience, 2025)

Health-promoting functions and related comprehensive molecular mechanisms of tea: from the perspectives of anti-inflammatory, lipid-lowering, glucose-lowering and anti-cancer effects - Jingguo Xu; Shiyao Jia; Yuting Ren; Yao Zhang; Junyan Zhang; Chao Tang; Juan Kan; Jun Liu; Yao Wang (Food Bioscience, 2025)

Digitally interactive smart textiles in football prepared by an outstanding viscose-based flexible strain sensor - Shidong Ma; Yuting Wu; Jian Tang; Jiayi Fu; Han Liu; Yumin Zhang; Jinyu Ma; Zhijuan Pan; Tao Yan (Chemical Engineering Journal, 2025)

The effects of high intensity exercise on pregnancy outcomes and complications during pregnancy: a meta-analysis of randomized controlled trials - Xinyuan Liu; Xian Guo; Rui Jie; Yuting Tang (European Journal of Applied Physiology, 2025)

Selection and validation of reference genes for quantitative real-time PCR analysis across tissues at different developmental stages in Taraxacum kok-saghyz - Yongmei Li; Yuan Yao; Tiancheng Xu; Xue Yang; Yuting He; Shengmin Zhang; Qingbiao Xie; Jie Cao; Chaorong Tang; Hui Liu (Journal of Plant Physiology, 2025)

Causality-Guided Deep learning for streamflow predicting in a mountainous region - Xuan Tang; Guanghua Qin; Xuemei Wu; Yuting Zhao; Hongxia Li (Journal of Hydrology, 2025)

Differential electrophysiological responses of wingless and winged forms of three non-host-alternating aphids to plant volatile compounds - Ya-Ya Li; Jinyue Qiao; Jicheng Wang; Xiujie Jia; Yuting Tang; Kairu Hou; Deguang Liu; Li Chen (Journal of Asia-Pacific Entomology, 2025)

An integrated framework for wildfire emergency response and post-fire debris flow prediction: a case study from the wildfire event on 20 April 2021 in Mianning, Sichuan, China - Yao Tang; Yuting Luo; Lijuan Wang; Ming Chen (Natural Hazards, 2025)

Gut metabolites and functional recovery after ischemic stroke: a genetic perspective - Wenpeng Wu; Luwen Zhu; Jiongliang Zhang; Xinyue Li; Donghui Yu; Yuting Wang; Yumeng Su; Xiangyu Wei; Hanwen Ma; Wenjing Song; Jinting Li; Lili Teng; et al. (Mammalian Genome, 2025)

Epidemiological characteristics of Helicobacter pylori infection and antibiotic resistance in urban areas of Guangdong Province, China: a multi-center, cross-sectional surveillance - Luhua Xian; Yuting Si; Luan Luan; Jinxin Lai; Jiawei Tang; Liang Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Research on the measurement and spatio-temporal evolution of marine new-quality productivity in China - Xiujuan Sha; Huimin Tang; Yuting Wang (Frontiers in Marine Science, 2025)
With the deepening development of the new round of technological revolution, marine new quality productive forces (MNQPF), as a key driver for promoting the high-quality development of China's marine economy, exhibit significant regional disparities in coastal areas. These disparities hold critical implications for formulating scientifically grounded regional development strategies. Based on the three constituent elements of Marxist productive forces, this study employs the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) entropy method, Gini coefficient, and kernel density estimation to analyze the spatial-temporal evolution of MNQPF levels across China's coastal provinces using panel data from 2012 to 2021. The findings reveal:(1) China's MNQPF has shown an upward trend, yet its overall level remains relatively low;(2) Regional imbalances persist, with the Eastern Marine Economic Circle outperforming the Southern and Northern counterparts. Regional disparities primarily stem from inter-regional differences and super-variable density;(3) Spatial heterogeneity characterizes MNQPF development, manifesting as "balanced growth in central regions vs. uneven development in northern and southern areas." In this regard, relevant discussion recommendations are put forward: (1) The Eastern Marine Economic Circle should leverage technological spillover effects to extend high-end marine industries northward to the Bohai Rim Economic Circle and southward to the Beibu Gulf Economic Zone;(2) The Northern Marine Economic Circle should advance green transformation of "marine + heavy industry" through port-economic belt construction under integrated land-sea development strategies;(3) The Southern Marine Economic Circle ought to enhance cross-border marine cooperation by capitalizing on its role as a "Belt and Road" hub, while strengthening Guangdong's radiating influence on neighboring provinces.

Continental evaluation of GPM IMERG V07B precipitation on a sub-daily scale - Jinghua Xiong; Guoqiang Tang; Yuting Yang (Remote Sensing of Environment, 2025)

Exposure to toxic metals might accelerate aging - Wenqing Wang; Kaixuan Yang; Jiayi Li; Yaoyao Lin; Man Rao; Yuting Zhang; Hazizi Duoliken; Mingjuan Jin; Jianbing Wang; Kun Chen; Mengling Tang (Environmental Research, 2025)

Surface passivated 3D halide perovskite single crystal by 2D perovskite towards high performance soft X-ray detection and gamma-ray spectrum - Yan Xiong; Min Li; Shunsheng Yuan; Yuting Liu; Tong Jin; Jincong Pang; Sihao Xia; Mingquan Liao; Lingling Liu; Lingfeng Wu; Kuan Yew Cheong; Huayang Yu; et al. (Chemical Engineering Journal, 2025)

Optimizing phase change heat dissipation for boosted output power and wearing comfort in thermoelectric generators - Chenyang Li; Dongwang Yang; Yutian Liu; Zinan Zhang; Jianan Lyu; Ziao Wang; Gang Zhan; Yuting Wang; Zhenming Li; Mingyang Liu; Wei Liu; Zhigang Ren; et al. (Chemical Engineering Journal, 2025)

Effects of Blood Cadmium Levels on Blood Pressure and the Risk of Hypertension in a Community-Based Elderly Population - Man Rao; Yuting Zhang; Hazizi Duoliken; Sitong Li; Mingjuan Jin; Jianbing Wang; Kun Chen; Mengling Tang (Exposure and Health, 2025)

Cavity as radio telescope for galactic dark photon - Yanjie Zeng; Yuxin Liu; Chunlong Li; Yuxiang Liu; Bo Wang; Zhenxing Tang; Yuting Yang; Liwen Feng; Peng Sha; Zhenghui Mi; Weimin Pan; Tianzong Zhang; et al. (Science Bulletin, 2025)

A β-cyclodextrin-based supramolecular modular system creating micellar carriers for codelivery of doxorubicin and siRNA for potential combined chemotherapy and immunotherapy - Xichuan Tang; Yuting Wen; Zhongxing Zhang; Xia Song; Jingling Zhu; Xuehao Tian; Jun Li (Carbohydrate Polymers, 2025)

Sodium bisulfite boosted exopolysaccharide production by Auxenochlorella protothecoides: Potential mechanisms harnessing H2O2 signaling and carbon reallocation - Rong Zhou; Wenli Zuo; Yuwei Xie; Yuting Wang; Chao Li; Yufang Tang; Zhenyao Wang; Yuqin Li (Bioresource Technology, 2025)

PKS1 involved in anthocyanin accumulation in red-skinned pear fruit - Lei Guo; Yuting Hao; Ying Tang; Mengjia Wu; Rui Zhai; Chengquan Yang; Lingfei Xu; Zhigang Wang (Plant Cell Reports, 2025)

Mechanisms and river blocking effects of clustering debris flows on 20 August 2019 along the Minjiang River, Wenchuan, China - Yuting Luo; Ming Chen; Lijuan Wang; Yao Tang; Song Ma (Journal of Earth System Science, 2025)

Correction: Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2025)

Recent advances in bioinspired multienzyme engineering for food applications - Xianhan Chen; Yujin Chen; Dandan Tang; Mengyu Li; Yuting Lu; Yi Cao; Quanyu Zhao; Shuai Jiang; Wei Liu; Ling Jiang (Trends in Food Science & Technology, 2025)

Enhancing walnut butter with a pea protein isolate-pectin-pterostilbene complex: Physicochemical properties and stability analysis - Zonghui Tang; Panchen Fang; Yuting Tao; Qiuye Huang; Xuefei Xu; Xiaoyan Cheng; Faraz Hussain; Xueling Li; Jin Liang; Shuming Ye; Yue Sun (Food Research International, 2025)

Improving physicochemical properties and gel formation mechanism of nutty plant-based yogurt with Tremella fuciformis polysaccharides - Ling Lin; Xiaoqing Qian; Junyu He; Yuting Shao; Yao Zeng; Mengxin Tang; Yong Fang; Xiaoyi Jiang; Jian Ding (Food Chemistry, 2025)

Design, synthesis and systemic acquired resistance of 2-benzothiadiazolylquinoline-4-carboxamides by COI1 based virtual screening - Xiaoyu Liu; Hongwei Yang; Yaru Sun; Yuting Huang; Shuang Hong; Haolin Yuan; Wei Gao; Liangfu Tang; Zhijin Fan (Molecular Diversity, 2025)

The Role of SIRT1–BDNF Signaling Pathway in Fluoride-Induced Toxicity for Glial BV-2 Cells - Bo Yang; Feiqing Wang; Xu Yang; Xiaoshuang Yuan; Yuting Yang; Xiaoxu Chen; Tingting Tian; Fa Chen; Dongxin Tang; Zhixu He; Yang Liu; Yanju Li (Biological Trace Element Research, 2025)

Unlocking the potential of vinegar residue: A novel biorefining strategy for amino acid-enriched xylooligosaccharides and humic-like acid - Yuanyuan Zhu; Ruijun Tang; Yuting Cao; Yongjian Yu; Junjun Zhu (Waste Management, 2025)

Interaction and bacterial effects of microplastics pollution on heavy metals in hyporheic sediments of different land-use types in the Beiluo River Basin - Bingjie Li; Zeyu Chen; Yuting Zhang; Ruichen Mao; Jinxi Song; Yongqing Long; Bin Tang; Jiayuan Feng; Myint Myint Nyein (Environmental Pollution, 2025)

Multifunctional nanofiber system with photothermal-controlled drug delivery and motion monitoring capabilities as intelligent wound dressing - Peiran Lin; Kaitong He; Jiahui Luo; Jiyuan Wang; Yuting Liu; Jian Zhang; Hao Fan; Shunfen Huang; Wei Lan; Wenlong Wang; Xuhui Zhang; Botao Gao; et al. (Chemical Engineering Journal, 2025)

Ultra-high pseudocapacitive contribution in free-standing O-Cu2Se/Cu electrode induces excellent kinetics and stability for sodium-ion storage - Yuting Tang; Fei Wang; Chang Nie; Haoxi Dong; Tingting Ma; Mingshu Zhao; Sen Yang (Chemical Engineering Journal, 2025)

The study on agitation and structure of orbitofrontal cortex subregion in first-episode drug-naïve patients with schizophrenia - Yingbo Dong; Congxin Chen; Yuting Li; Peiyu Cao; Yilin Tang; Guoxin Xu; Qi Si; Runda Li; Yuxiu Sui (Brain Imaging and Behavior, 2024)

Multiple effects of submerged plants on microplastics-heavy metals redistribution and combination in the hyporheic sediment - Zeyu Chen; Bingjie Li; Jinxi Song; Yuting Zhang; Haotian Sun; Nan Li; Bin Tang (Journal of Hazardous Materials, 2024)

Preparation of nano-Al2O3 support CaO-based sorbent pellets by novel methods for high-temperature CO2 capture - Weilong Chen; Yuting Tang; Hongyu Liu; Jiehong Tang; Jingmin Deng; Ziwei Sun; Xiaoqian Ma (Journal of Environmental Chemical Engineering, 2024)

Carvacrol acts on the larval midgut of Spodoptera frugiperda by destroying the tissue structure and altering the bacterial community - Jingjing Zhang; Cuiting Liu; Xinyi Xie; Xuanyue Yu; Yuting Huang; Rui Tang; Jian Zeng; Benshui Shu (Journal of Asia-Pacific Entomology, 2024)

STAT3 Inhibitor Increases α-Synuclein in PFF-Treated Astroglia Cells by Dysregulating Autophagy and Potentially Affects Exosome Biogenesis - Yangfu Luo; Nailiang Zang; Yuting Tang; Hao Chen; Hanqun Liu; Lan Wang; Pingyi Xu (NeuroMolecular Medicine, 2024)

Exogenous paths regulate electron transfer enhancing sediment phosphorus immobilization - Lean Zhou; Yuting Zeng; Chong Xu; Naif Abdullah Al-Dhabi; Shu Wang; Shiquan Sun; Jinting Wang; Wangwang Tang; Tian Li; Xin Wang (Science of The Total Environment, 2024)

Natural background level, source apportionment and health risk assessment of potentially toxic elements in multi-layer aquifers of arid area in Northwest China - Rongwen Yao; Yunhui Zhang; Yuting Yan; Xiangchuan Wu; Md Galal Uddin; Denghui Wei; Xun Huang; Lijun Tang (Journal of Hazardous Materials, 2024)

Biodiversity-safeguarding threshold for urea-fertilizer application on paddy fields: Protozoa-based toxicity tests - Chunyu Hou; Kexin Yu; Tianyi Shi; Benchao Jiang; Liangzi Cao; Wenyuan Wang; Mei Han; Jing Tang; Yuting Zhao; Xuming Pan; Jianye Li; Duu-Jong Lee; et al. (Journal of Environmental Management, 2024)

Vegetation restoration enhancing soil carbon sequestration in karst rocky desertification ecosystems: A meta-analysis - Wei Zheng; Xiaobin Guo; Ping Zhou; Li Tang; Jiaxin Lai; Yuting Dai; Wende Yan; Jinshui Wu (Journal of Environmental Management, 2024)

Red mud enhanced biomass gasification to produce syngas: Mechanism, simulation and economic evaluation - Hongyu Liu; Yuting Tang; Xiaoqian Ma; Jiehong Tang; Wenchang Yue; Weilong Chen; Ziwei Sun; Jingmin Deng (Chemical Engineering Journal, 2024)

Nrf2 affects DNA damage repair and cell apoptosis through regulating HR and the intrinsic Caspase-dependent apoptosis pathway in TK6 cells exposed to hydroquinone - Lin Chen; Pu Guo; Lu Zhai; Lingxue Yu; Delong Zhu; Xiaoyi Hu; Zhuanzhuan Li; Yuting Chen; Qian Sun; Lei Sun; Hao Luo; Huanwen Tang (Toxicology in Vitro, 2024)

Ions release stages of Cu-Pb-Zn mine tailings waste: A column leaching simulation - Lei Xu; Liang Tang; Zeming Shi; Jingsong Yang; Kunhao Shi; Haili Zhang; Yuting Yuan (Ore and Energy Resource Geology, 2024)

Oxygen evolution reaction enhancing electrochemical performance of V-doped Ni(OH)2 for aqueous asymmetric supercapacitors - Ting Xiao; Hongxiang Lin; Can Tang; Xiuru Li; Yuting Mei; Lin Gao; Lihua Jiang; Peng Xiang; Shibing Ni; Yequan Xiao; Xinyu Tan (Chemical Engineering Journal, 2024)

Lanthanum ferrite modified filling materials and its enhancement for phosphorus and COD removal: Performance and mechanism - Qing Li; Bei Yang; Xinyu Chen; Yuting Han; Qin Chen; Shiying He; Yanfang Feng; Yancan Wu; Xiaohui Liang; Lihong Xue; Jie Tang (Journal of Water Process Engineering, 2024)

Urea-modified hazelnut shell biochar (N-HSB) for efficient Cr(VI) removal: Performance and mechanism insights - Yuting Zhang; Yuwei Tang; Baoming Jin; Ruiping Yan; Li Zhang; Yilong Li; Jinchunzi Li; Shuang Liang (Journal of Contaminant Hydrology, 2024)

Prenatal triphenyl phosphate exposure impairs placentation and induces preeclampsia-like symptoms in mice - Qian Liu; Mengzhu Jiang; Xiaoxun Lu; Jiabin Hong; Yanqin Sun; Chun Yang; Yuting Chen; Xingxing Chai; Huanwen Tang; Xiaoshan Liu (Environmental Research, 2024)

Suppression of pathological neovascularization by anti-Flt1 peptide functionalized DNA tetrahedron - Bicai Tang; Yuting Yang; Yong Li; Yutian He; Yichen Ge; Yangxue Yao; Wenjuan Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Influence of group VIB metals introduced into zeolite on the adsorption performance of VOCs in cooking oil fumes - Honghong Yi; Siming Guo; Yuting Yuan; Qingjun Yu; Fengshi Meng; Wenjing Wu; Shunzheng Zhao; Ya Wang; Xiaolong Tang (Chemical Engineering Journal, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

The competition of heavy metals between hyporheic sediments and microplastics of driving factors in the Beiluo River Basin - Bingjie Li; Ruichen Mao; Zeyu Chen; Yuting Zhang; Jinxi Song; Nan Li; Bin Tang; Jiayuan Feng; Mingchang Guan (Journal of Hazardous Materials, 2024)

Cocrystal Prediction of Nifedipine Based on the Graph Neural Network and Molecular Electrostatic Potential Surface - Yuting Wang; Yanling Jiang; Yu Zhou; Huai He; Jincao Tang; Anqing Luo; Zeng Liu; Chi Ma; Qin Xiao; Tianbing Guan; Chuanyun Dai (AAPS PharmSciTech, 2024)

Recent advance in technological innovations of sugar-reduced products - Gaopeng Zhang; Lyu Zhang; Ishtiaq Ahmad; Jianyou Zhang; Anqiang Zhang; Wei Tang; Yuting Ding; Fei Lyu (Critical Reviews in Food Science and Nutrition, 2024)

Airborne environmentally persistent free radicals (EPFRs) in PM2.5 from combustion sources: Abundance, cytotoxicity and potential exposure risks - Zhen Zhao; Hanhan Li; Yaqian Wei; Guodong Fang; Qian Jiang; Yuting Pang; Weijie Huang; Mingwei Tang; Yuanshu Jing; Xinyuan Feng; Xiao-San Luo; Thomas Berkemeier (Science of The Total Environment, 2024)

Sophisticated construction of single-atom cobalt catalyst based on microbial hyphae for high-performance hydrogenation - Junhua Kuang; Minghao Gong; Gaofeng Chen; Li Peng; Chen Zou; Zhiqing Peng; Weiming Chen; Yin Li; Yuting Zhang; Tianwei Xue; Chuang Li; Yangyang Dong; et al. (Chemical Engineering Journal, 2024)

Catalysis derived from three-dimensionally ordered macroporous Nb2O5 towards the hydrogen storage performance of magnesium hydride - Yan Chen; Yuting Shao; Yana Liu; Haiguang Gao; Qinke Tang; Yunfeng Zhu; Jiguang Zhang; Jun Wang; Liquan Li; Xiaohui Hu (Fuel, 2024)

Immediate and delayed effects of environmental temperature on schizophrenia admissions in Liuzhou, China, 2013–2020: a time series analysis - Qian Zhou; Xiaolan Huang; Li Su; Xianyan Tang; Yanli Qin; Yuting Huo; Chun Zhou; Jun Lan; Yue Zhao; Zaifei Huang; Guoguang Huang; Yuhua Wei (International Journal of Biometeorology, 2024)

Interspecific occupancy-abundance relationship of benthic diatoms changes seasonally with attachment mode in a tropical river - Lin Tan; Yuting Liu; Muqi Shen; Guifeng Wei; Linglin Wan; Quehui Tang; Bo-Ping Han (Hydrobiologia, 2024)

Exploring interactive and nonlinear effects of key factors on intercity travel mode choice using XGBoost - Xiaowei Li; Lanxin Shi; Yang Shi; Junqing Tang; Pengjun Zhao; Yuting Wang; Jun Chen (Applied Geography, 2024)

New insight into identifying sediment phosphorus sources in multi-source polluted urban river: Effect of environmental-induced microbial community succession on stability of microbial source tracking results - Wenlong Zhang; Zikang Tang; Yuting Yan; Chenyue Sun; Dan He; Yi Li (Environmental Research, 2024)

Novel ROS-scavenging hydrogel produced in situ crosslinking between cyclodextrin and cellulose for promoting diabetic wound healing - Yuting Zhang; Tian Si; Shengbao Cai; Xin Gao; Xiaoning Tang; Lincai Peng; Ze Chen; Qiuyue Hu; Jiaqi Li; Heng Zhang (Chemical Engineering Journal, 2024)

Human CYP1A1-activated aneugenicity of aflatoxin B1 in mammalian cells and its combined effect with benzo(a)pyrene - Huanhuan Wang; Qin Fan; Qian Liang; Yao Wu; Zhongming Ye; Haipeng Wu; Qian Sun; Huanwen Tang; Yungang Liu; Qizhan Liu; Yuting Chen (Chemico-Biological Interactions, 2024)

An Understanding of the Relationship Between Mixing Performance and Power Consumption in a High-Shear Wet Granulation Pre-mixing - Zeng Liu; Chunling Liu; Renyu Fan; Yuting Wang; Linxiu Luo; Yanling Jiang; Jincao Tang; Zheng Lu; Libo Chen; Shuangkou Chen; Tianbing Guan; Chuanyun Dai (Journal of Pharmaceutical Innovation, 2024)

Alterations in sperm DNA methylation may as a mediator of paternal air pollution exposure and offspring birth outcomes: Insight from a birth cohort study - Yuting Cheng; Jialin Feng; Jing Wang; Yijie Zhou; Shengjun Bai; Qiuqin Tang; Jinhui Li; Feng Pan; Qiaoqiao Xu; Chuncheng Lu; Wei Wu; Yankai Xia (Environmental Research, 2024)

Gradient optimization method for tunnel resistivity and chargeability joint inversion based on deep learning - Peng Jiang; Benchao Liu; Yuting Tang; Zhengyu Liu; Yonghao Pang (Tunnelling and Underground Space Technology, 2024)

Spatiotemporal differences in tropospheric ozone sensitivity and the impact of “dual carbon” goal - Yuting Liu; Guiqian Tang; Yinghong Wang; Mengtian Cheng; Jian Gao; Yuesi Wang (Science Bulletin, 2024)

AaABCG20 transporter involved in cutin and wax secretion affects the initiation and development of glandular trichomes in Artemisia annua - Xueqing Fu; Han Zheng; Yuting Wang; Hang Liu; Pin Liu; Ling Li; Jingya Zhao; Xiaofen Sun; Kexuan Tang (Plant Science, 2024)

Research on bidirectional fluid-structure interaction characteristics of horizontal axis tidal turbines under wave current conditions - Ruizhang Huang; Shuqi Wang; Yuting Lu; Ji Tang; Wei Guo (Ocean Engineering, 2024)

Quantitative assessment of expected direct economic losses of buildings for debris flows in multiple rainfall intensity scenarios in Yangling Gully, Southwest China - Ming Chen; Yuting Luo; Chuan Tang; Ning Li (Natural Hazards, 2024)

Effects of exercise, metformin, and combination treatments on type 2 diabetic mellitus-induced muscle atrophy in db/db mice: Crosstalk between autophagy and the proteasome - Mengqi Xiang; Xinmeng Yuan; Nianyun Zhang; Liumei Zhang; Yuting Liu; Jingjing Liu; Yaran Gao; Ye Xu; Wen Sun; Qiang Tang; Yuan Zhang; Jiao Lu (Journal of Physiology and Biochemistry, 2024)

How changes in landscape patterns affect the carbon emission: a case study in the Chengdu-Chongqing Economic Circle, China - Zhonglin Tang; Yang Xiao; Yuting Wang; Yezi Xu; Bingnan Ren; Geng Sun (Environmental Monitoring and Assessment, 2024)

Exposure to particulate matter may affect semen quality via trace metals: Evidence from a retrospective cohort study on fertile males - Yuting Cheng; Jiaqi Zhu; Qiuqin Tang; Jing Wang; Jialin Feng; Yijie Zhou; Jinhui Li; Feng Pan; Xiumei Han; Chuncheng Lu; Xinru Wang; Marvin E. Langston; et al. (Chemosphere, 2024)

With spatial distribution, risk evaluation of heavy metals and microplastics to emphasize the composite mechanism in hyporheic sediments of Beiluo River - Bingjie Li; Jinxi Song; Mingchang Guan; Zeyu Chen; Bin Tang; Yongqing Long; Ruichen Mao; Jiawei Zhao; Wenjin Xu; Yuting Zhang (Journal of Hazardous Materials, 2024)

Vertical distribution of VOCs in the boundary layer of the Lhasa valley and its impact on ozone pollution - Dan Yao; Yinghong Wang; Zhixuan Bai; Mengtian Cheng; Guiqian Tang; Yuting Liu; Deqing Zhuoga; Hao Yu; Jianchun Bian; Yuesi Wang (Environmental Pollution, 2024)

Exosomal derived miR-1246 from hydroquinone-transformed cells drives S phase accumulation arrest by targeting cyclin G2 in TK6 cells - Yuting Chen; Lin Chen; Shiheng Zhu; Hui Yang; Zhongming Ye; Huanhuan Wang; Haipeng Wu; Yao Wu; Qian Sun; Xiaoshan Liu; Hairong Liang; Huanwen Tang (Chemico-Biological Interactions, 2024)

Diverse chemical components of PM10 emitted from different coal combustions resulting in distinct cytotoxicity - Weijie Huang; Xiao-San Luo; Yuting Pang; Mingwei Tang; Zhen Zhao; Hanhan Li (Fuel, 2023)

MiR-7-5p targeted Rb regulating cell cycle is involved in hydroquinone-induced malignant progression in human lymphoblastoid TK6 cells - Lu Zhai; Yuting Gao; Zheming Cui; Lin Chen; Lingxue Yu; Pu Guo; Delong Zhu; Huanwen Tang; Xin Liu; Hao Luo (Food and Chemical Toxicology, 2023)

Reducing spatial resolution increased net primary productivity prediction of terrestrial ecosystems: A Random Forest approach - Tao Zhou; Yuting Hou; Zhihan Yang; Benjamin Laffitte; Ke Luo; Xinrui Luo; Dan Liao; Xiaolu Tang (Science of The Total Environment, 2023)

Rationally designed multifunctional nanoparticles as GSH-responsive anticancer drug delivery systems based on host-guest polymers derived from dextran and β-cyclodextrin - Xichuan Tang; Yuting Wen; Zhongxing Zhang; Jingling Zhu; Xia Song; Jun Li (Carbohydrate Polymers, 2023)

Carbon emissions induced by land use and land cover change amid rapid urbanization in Chengdu-Chongqing economic circle, China: efficiency, transfer and process - Zhonglin Tang; Shan Ma; Min Fu; Yuting Wang; Jingyue Xue; Yuanfu Yin; Yang Xiao (Environment, Development and Sustainability, 2023)

Molecular Identification and Expression Analysis of an Intelectin Gene in the Yellow Catfish Pelteobagrus fulvidraco (Siluriformes: Bagridae) - Senhao Jiang; Yuting Lei; Yanxuan Li; Wanyan Sun; Ti Wang; Ruiting Ma; Qiuning Liu; Boping Tang (Fishes, 2023)
Intelectins (ITLNs) are a family of calcium-dependent lectins with carbohydrate-binding capacity, are distributed across various vertebrates, and play an important role in the innate immune response against pathogen infection. The yellow catfish Pelteobagrus fulvidraco (Siluriformes: Bagridae) is an economically important fish in China. The aim of this study was to quantify the gene expression of ITLN in response to pathogen-associated molecular patterns (PAMPs) stimulation. Here, the ITLN gene of P. fulvidraco was characterized and named PfITLN. The full-length cDNA of PfITLN was 1132 bp, including a 5’-untranslated region (UTR) of 140 bp, a 3’-UTR of 110 bp, and an open reading frame (ORF) of 882 bp encoding a polypeptide of 293 amino acids, which contains a signal peptide and two fibrinogen-related domains (FReDs). PfITLN had a molecular weight of 32.39 kDa with a theoretical pI of 5.03. The deduced PfITLN amino acid sequence had 81%, 64%, and 55% homology with Ictalurus furcatus, Danio rerio, and Homo sapiens, respectively. Moreover, the predicted tertiary protein structure of PfITLN was highly similar to that of other animals, and phylogenetic analysis showed that the PfITLN protein was close to those of other Teleostei. Real-time quantitative reverse transcription-PCR (qRT-PCR) analysis showed PfITLN expression in all examined tissues, with the highest abundance seen in the liver, followed by the head kidney, spleen, trunk kidney, and muscle. After PAMP infection with lipopolysaccharide (LPS) and polyriboinosinic polyribocytidylic acid (poly I:C), the expression levels of PfITLN were significantly upregulated at different time points. These results suggested that PfITLN might be involved in innate immunity.

Life cycle assessment of the solid oxide fuel cell vehicles using ammonia fuel - Chengfeng Liao; Yuting Tang; Yuchen Liu; Ziwei Sun; Weijie Li; Xiaoqian Ma (Journal of Environmental Chemical Engineering, 2023)

Effect of cryoprotectants on physicochemical and structural changes in repeated freeze–thawed egg white protein - Gaopeng Zhang; Chunyan Zhu; Noman Walayat; Wei Tang; Yonggang Tu; Yuting Ding; Jianhua Liu (Food Bioscience, 2023)

Calcium signaling-mediated transcriptional reprogramming during abiotic stress response in plants - Huimin Ren; Yuting Zhang; Minyi Zhong; Jamshaid Hussian; Yuting Tang; Shenkui Liu; Guoning Qi (Theoretical and Applied Genetics, 2023)

Removal performance and mechanisms of aqueous Cr (VI) by biochar derived from waste hazelnut shell - Yuting Zhang; Yuwei Tang; Ruiping Yan; Jinchunzi Li; Chenyang Li; Shuang Liang (Environmental Science and Pollution Research, 2023)

Single-cell RNA sequencing to reveal non-parenchymal cell heterogeneity and immune network of acetaminophen-induced liver injury in mice - Xiaoyun Li; Yang Zhi; Jing Li; Xiaohong Lei; Yi Ju; Yuting Zhang; Yufan Zheng; Xiaming Kong; Feng Xue; Wei Zhong; Xiaoyu Chen; Jieting Tang; et al. (Archives of Toxicology, 2023)

A simple AIE-active salicylideneaniline towards bimodal encryption-decryption with unique ESIPT-inhibited amorphous state - Xu-Min Cai; Weiren Zhong; Ziwei Deng; Yuting Lin; Zhenguo Tang; Xuedan Zhang; Jianyu Zhang; Wenjin Wang; Shenlin Huang; Zheng Zhao; Ben Zhong Tang (Chemical Engineering Journal, 2023)

Coseismic gravitational curvatures changes in a spherical symmetric Earth model - Yuting Ji; Robert Tenzer; He Tang; Wenke Sun (Physics of the Earth and Planetary Interiors, 2023)

Future hotter summer greatly increases residential electricity consumption in Beijing: A study based on different house layouts and shared socioeconomic pathways - Qiyuan Hu; Jiayue Tang; Xiang Gao; Sijia Wang; Dan Zhang; Yuting Qin; Qihan Wang; Yi Zhou; Na Huang; Josep Penuelas; Jordi Sardans; Josep G. Canadell; et al. (Sustainable Cities and Society, 2023)

Dephosphorylation of CatC at Ser-18 improves salt and oxidative tolerance via promoting its tetramerization in rice - Yan Wang; Yuting Yi; Cong Liu; Heping Zheng; Jian Huang; Ye Tian; Huihui Zhang; Qiang Gao; Dongying Tang; Jianzhong Lin; Xuanming Liu (Plant Science, 2023)

Natural-human driving factors of groundwater salinization in a long-term irrigation area - Yuting Zhang; Kai Hou; Hui Qian; Yanyan Gao; Yuan Fang; Shunqi Tang; Shan Xiao; Wenhao Ren; Wengang Qu; Qiying Zhang (Environmental Research, 2023)

Self-destructive microchip: Support-free energetic film of BiOBr/Al/Bi2O3 nanothermites and its destructive performance - Haifeng Yang; Zhiqiang Qiao; Weimiao Wang; Pengfei Tang; Shuaishuai Man; Xiaodong Li; YuTing Xie; Deyun Tang; Xueming Li; Guangcheng Yang (Chemical Engineering Journal, 2023)

Corrigendum to “miR-7-5p overexpression suppresses cell proliferation and promotes apoptosis through inhibiting the ability of DNA damage repair of PARP-1 and BRCA1 in TK6 cells exposed to hydroquinone” [Chem. Biol. Interact. 283 (2018) 84–90] - Hao Luo; Hairong Liang; Yuting Chen; Shaoyun Chen; Yongchun Xu; Longmei Xu; Jiaxian Liu; Kairu Zhou; Jucheng Peng; Guoqiang Guo; Bei Lai; Li Song; et al. (Chemico-Biological Interactions, 2023)

Impact of salt deposition induced by water evaporation on petrophysical properties and pore structure in underground gas storage through dynamic and static experiments - Yong Tang; Ning Wang; Youwei He; Yong Wang; Yuting Shan; Haochuan Zhang; Yu Sun (Journal of Hydrology, 2023)

The disintegration mechanism analysis of soft rock due to water intrusion based on discrete element method - Haitao Yu; Zhibin Liu; Yun Zhang; Tingyi Luo; Yasen Tang; Qingsong Zhang; Yuting Wang (Computers & Geosciences, 2023)

Human CYP1B1 enzyme-mediated, AhR enhanced activation of aflatoxin B1 for its genotoxicity in human cells - Yuting Chen; Zhaohong Lu; Boxin Li; Huanhuan Wang; Tikeng Jiang; Mei Xuan; Hui Yang; Jialong Chen; Xiaoshan Liu; Hairong Liang; Yungang Liu; Huanwen Tang (Toxicology Letters, 2023)

Filling the gap between molecular and aggregate states: how does molecular packing affect photophysical properties? - Xu-Min Cai; Yuting Lin; Zhenguo Tang; Xuedan Zhang; Tianqi Mu; Shenlin Huang; Zheng Zhao; Ben Zhong Tang (Chemical Engineering Journal, 2023)

Disruption of RBMS3 suppresses PD-L1 and enhances antitumor immune activities and therapeutic effects of auranofin against triple-negative breast cancer - Yuting Zhou; Zhongping Liang; Yingjie Xia; Shuai Li; Jiali Liang; Zhixiang Hu; Chengbin Tang; Qing Zhao; Qing Gong; Yongchang Ouyang (Chemico-Biological Interactions, 2023)

Emerging electrocatalytic activities in transition metal selenides: synthesis, electronic modulation, and structure-performance correlations - Yuting Deng; Sutong Xiao; Yijuan Zheng; Xiao Rong; Mingru Bai; Yuanjiao Tang; Tian Ma; Chong Cheng; Changsheng Zhao (Chemical Engineering Journal, 2023)

Coupling Relationship of Geomorphic Evolution and Marine Hydrodynamics in the Stage-Specific Development of Urban Bays: A Modelling Case Study in Quanzhou Bay (1954–2017), China - Xianbiao Xiao; Yunhai Li; Junjian Tang; Fusheng Luo; Fangfang Shu; Liang Wang; Jia He; Xiaochun Zou; Wenqi Chi; Yuting Lin; Binxin Zheng (Journal of Marine Science and Engineering, 2022)
With the development of social economy and human activities, the geomorphology and hydrodynamic conditions of coasts have been dramatically changed, causing serious environmental pollution and resource depletion. Taking Quanzhou Bay as an example, this study combined geomorphologic change with a hydrodynamic model to simulate the change in tidal currents in different periods. The results show a change in the coastline was the main cause of hydrodynamic change during the industrialization reform. During the past 70 years, the tidal prism decreased year by year, and the average velocity of the tidal current in the channel decreased by 33.7% and 30.8% at flood and ebb tide, respectively. In the early stages of industrialization, reclamation land was used in a single way. The tidal prism decreased by 22.2% and 29.8% in the spring and neap tide, respectively. In the middle and later stages, the tidal current velocity increased, and reclamation land was used in a variety of ways. In modern society, the reclamation land-use type was unitary. Based on this research, we show the influence of human activities on the evolution of the bay’s geomorphology and provide suggestions for the management of the bay.

Degradation of dibutyl phthalate by ozonation in the ultrasonic cavitation–rotational flow interaction coupled-field: performance and mechanism - Huan Zhang; Bing Wang; Pan Tang; Yuting Lu; Chunyang Gao (Environmental Science and Pollution Research, 2022)

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

Coffin-Siris syndrome in two chinese patients with novel pathogenic variants of ARID1A and SMARCA4 - Mingjie Liu; Linlin Wan; Chunrong Wang; Hongyu Yuan; Yun Peng; Na Wan; Zhichao Tang; Xinrong Yuan; Daji Chen; Zhe Long; Yuting Shi; Rong Qiu; et al. (Genes & Genomics, 2022)

The activity, segmentation, and evolution characteristics of large-scale landslides along the Anninghe active fault zone, Southwest China - Hongfu Zhou; Fei Ye; Wenxi Fu; Yuting Wei; Yadong Qin; Wenqing Tang; Tian Fang (Bulletin of Engineering Geology and the Environment, 2022)

An inactivating mutation in the vacuolar arginine exporter gene Vae results in culture degeneration in the fungus Metarhizium robertsii - Hui Song; Yuting Bao; Mingxiang Zhang; Shuxing Liu; Chaonan Yu; Jin Dai; Congcong Wu; Dan Tang; Weiguo Fang (Environmental Microbiology, 2022)
Summary Culture degeneration usually results in great commercial losses in the economically important filamentous fungi, but the genetic causes of the degeneration remain elusive. In the fungus Metarhizium robertsii , we found that deletion of the vacuolar arginine exporter gene Vae caused culture degeneration. Compared to the WT strain, the mutant showed increased apoptosis, reactive oxygen species (ROS) level and mitochondrial membrane potential collapse, reduced conidial yield and abnormal lipid droplet formation. The extent of the degeneration in the mutant gradually increased over the successive subculturing, which eventually became irreversible; compared to the third subculture of the mutant, the seventh subculture showed a lower conidial yield and pathogenicity to insects, stronger apoptosis, higher ROS level and a smaller number of conidial lipid droplets. Incorporation of the genomic clone of Vae could not restore the WT phenotypes in the seventh subculture, but could in the third one. Loss‐of‐function in Vae resulted in vacuolar arginine accumulation and reduction in the cytosolic arginine. This downregulated the expression of the regulator CAG9 of G protein signalling pathway, which accounted for most of the phenotypic changes associated with the degeneration of the mutant. We identified a deleterious mutation that causes culture degeneration in a filamentous fugus.

First report of Neovaginatispora fuckelii causing stem blight on Rosa chinensis in China - Yuting Han; Jianxin Chen; Jie Tang; Zejia Lv; Yuan Zheng; Huancheng Ma; Jianrong Wu (Journal of Plant Pathology, 2021)

Artemisinin analogue SM934 protects against lupus-associated antiphospholipid syndrome via activation of Nrf2 and its targets - Zemin Lin; Yuting Liu; Li Chen; Shiqi Cao; Yueteng Huang; Xiaoqian Yang; Fenghua Zhu; Wei Tang; Shijun He; Jianping Zuo (Science China Life Sciences, 2021)

Numerical study of the building pressure cycling method for evaluating vapor intrusion from groundwater contamination - Yanqiu Liu; Jun Man; Yue Wang; Yuting Xiao; Wei Tang; Qiang Chen; Yijun Yao (Environmental Science and Pollution Research, 2020)

Establishment and characterization of an immortalized human chondrocyte cell line - Jiashu Yang; Yuting Tang; Wensun Chen; Ming Zhang; Fangling Hong; Dawei Yang; Qianyi Bao; Ying Yang; Yucui Jin; Lingyun Li; Changyan Ma (Biotechnology Letters, 2020)

A review of microplastics in the aquatic environmental: distribution, transport, ecotoxicology, and toxicological mechanisms - Jia Du; Shaodan Xu; Qingwei Zhou; Huanxuan Li; Li Fu; Junhong Tang; Yangyang Wang; Xu Peng; Yuting Xu; Xinpeng Du (Environmental Science and Pollution Research, 2020)

Model updating for real time dynamic substructures based on UKF algorithm - Su Tingli; Tang Zhenyun; Peng Lingyun; Bai Yuting; Jin Xuebo; Kong Jianlei (Earthquake Engineering and Engineering Vibration, 2020)

Dual-network design to enhance the properties of agar aerogel adsorbent by incorporating in situ ion cross-linked alginate - Dajian Huang; Qiling Quan; Yuting Zheng; Wenjie Tang; Zhuo Zhang; Xiaohu Qiang (Environmental Chemistry Letters, 2020)

Stress associated protein 1 regulates the development of glandular trichomes in Artemisia annua - Yuting Wang; Xueqing Fu; Lihui Xie; Wei Qin; Ling Li; Xiaofen Sun; Shihai Xing; Kexuan Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Straw biochar strengthens the life strategies and network of rhizosphere fungi in manure fertilized soils - Dandan Wang; Na Zhang; Haoqi Tang; Jonathan M. Adams; Bo Sun; Yuting Liang (Soil Ecology Letters, 2019)

Immunity induced by recombinant attenuated IHNV (infectious hematopoietic necrosis virus)‐G N438A expresses VP2 gene‐encoded IPNV (infectious pancreatic necrosis virus) against both pathogens in rainbow trout - Yaping Chen; Mengting Guo; Yanxue Wang; Xiaojing Hua; Shuai Gao; Yuting Wang; Dechuan Li; Wen Shi; Lijie Tang; Yijing Li; Min Liu (Journal of Fish Diseases, 2019)
Infectious hematopoietic necrosis virus (IHNV) and infectious pancreatic necrosis virus (IPNV) are important pathogens in rainbow trout farming worldwide. Their co‐infection is also common, which causes great economic loss in juvenile salmon species. Development of a universal virus vaccine providing broadly cross‐protective immunity will be of great importance. In this study, we generated two recombinant (r) virus (rIHNV‐N438A‐ΔNV‐EGFP and rIHNV‐N438A‐ΔNV‐VP2) replacing the NV gene of the backbone of rIHNV at the single point mutation at residue 438 with an efficient green fluorescent protein ( EGFP ) reporter gene and antigenic VP2 gene of IPNV. Meanwhile, we tested their efficacy against the wild‐type (wt) IHNV HLJ‐09 virus and IPNV serotype Sp virus challenge. The relative per cent survival rates of two recombinant viruses against (wt) IHNV HLJ‐09 virus challenge were 84.6% and 81.5%, respectively. Simultaneously, the relative per cent survival rate of rIHNV‐N438A‐ΔNV‐VP2 against IPNV serotype Sp virus challenge was 88.9%. It showed the two recombinant viruses had high protection rates and induced a high level of antibodies against IHNV or IPNV. Taken together, these results suggest the VP2 gene of IPNV can act as candidate gene for vaccine and attenuated multivalent live vaccines and molecular marker vaccines have potential application for viral vaccine.

Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2019)

Progesterone PLGA/mPEG-PLGA Hybrid Nanoparticle Sustained-Release System by Intramuscular Injection - Bin Xie; Yang Liu; Yuting Guo; Enbo Zhang; Chenguang Pu; Haibing He; Tian Yin; Xing Tang (Pharmaceutical Research, 2018)

In Vitro-In Vivo Relationship of Amorphous Insoluble API (Progesterone) in PLGA Microspheres - Chenguang Pu; Qiao Wang; Hongjuan Zhang; Jingxin Gou; Yuting Guo; Xinyi Tan; Bin Xie; Na Yin; Haibing He; Yu Zhang; Yanjiao Wang; Tian Yin; et al. (Pharmaceutical Research, 2017)

Injectable Sustained-Release Depots of PLGA Microspheres for Insoluble Drugs Prepared by hot-Melt Extrusion - Yuting Guo; Yunning Yang; Luying He; Rong Sun; Chenguang Pu; Bin Xie; Haibing He; Yu Zhang; Tian Yin; Yanjiao Wang; Xing Tang (Pharmaceutical Research, 2017)

Retraction Note to: The Clinical Utility of Matrix Metalloproteinase 9 in Evaluating Pathological Grade and Prognosis of Glioma Patients: A Meta-Analysis - Xiangshan Yang; Shunzeng Lv; Yuting Liu; Daotang Li; Ranran Shi; Zhenyu Tang; Jianzhen Fan; Zhongfa Xu (Molecular Neurobiology, 2017)

Retraction Note to: The Impact of Survivin on Prognosis and Clinicopathology of Glioma Patients: A Systematic Meta-Analysis - Shunzeng Lv; Congxin Dai; Yuting Liu; Ranran Shi; Zhenyu Tang; Mingzhi Han; Ruixiang Bian; Bowen Sun; Renzhi Wang (Molecular Neurobiology, 2017)

Calmodulin kinase II inhibitor regulates calcium homeostasis changes caused by acute β-adrenergic receptor agonist stimulation in mouse ventricular myocytes - Yan Huang; Tao Liu; Dandan Wang; Xin Wang; Ran Li; Yuting Chen; Yanhong Tang; Teng Wang; Congxin Huang (In Vitro Cellular & Developmental Biology - Animal, 2016)

High Serum GFAP Levels in SCA3/MJD May Not Correlate with Disease Progression - Yuting Shi; Chunrong Wang; Fengzhen Huang; Zhao Chen; Zhanfang Sun; Junling Wang; Beisha Tang; Tetsuo Ashizawa; Thomas Klockgether; Hong Jiang (The Cerebellum, 2015)

RETRACTED ARTICLE: The Clinical Utility of Matrix Metalloproteinase 9 in Evaluating Pathological Grade and Prognosis of Glioma Patients: A Meta-Analysis - Xiangshan Yang; Shunzeng Lv; Yuting Liu; Daotang Li; Ranran Shi; Zhenyu Tang; Jianzhen Fan; Zhongfa Xu (Molecular Neurobiology, 2015)

RETRACTED ARTICLE: The Impact of Survivin on Prognosis and Clinicopathology of Glioma Patients: A Systematic Meta-Analysis - Shunzeng Lv; Congxin Dai; Yuting Liu; Ranran Shi; Zhenyu Tang; Mingzhi Han; Ruixiang Bian; Bowen Sun; Renzhi Wang (Molecular Neurobiology, 2015)

Research on the thermal conductivity and moisture migration characteristics of Shanghai mucky clay. I: Experimental modeling - Yiqun Tang; Jie Zhou; Modan Zhang; Yuting Liu (Bulletin of Engineering Geology and the Environment, 2015)

Exploring the Wnt Pathway-Associated LncRNAs and Genes Involved in Pancreatic Carcinogenesis Driven by Tp53 Mutation - Qi Wang; He Jiang; Chen Ping; Ruizhe Shen; Tingting Liu; Juanjuan Li; Yuting Qian; Yanping Tang; Shidan Cheng; Weiyan Yao; Lifu Wang (Pharmaceutical Research, 2015)

Ac-cel, a Novel Antioxidant, Protects Against Hydrogen Peroxide-induced Injury in PC12 Cells via Attenuation of Mitochondrial Dysfunction - Xianjun Guo; Yuting Chen; Qunfang Liu; Jian Wu; Luoyi Wang; Xican Tang; Weimin Zhao; Haiyan Zhang (Journal of Molecular Neuroscience, 2013)

Rapid Evolution of Simple Sequence Repeat Induced by Allopolyploidization - Zongxiang Tang; Shulan Fu; Zhenglong Ren; Yuting Zou (Journal of Molecular Evolution, 2009)

Human epidermoid A431 cells express functional nicotinic Acid receptor HM74a - Lubing Zhou; Yuting Tang; Ellen V. Cryan; Keith T. Demarest (Molecular and Cellular Biochemistry, 2007)